Brainstroming Optimalisasi Manajemen Risiko Operasional Pada Layanan Mobile Banking Dalam Meningkatkan Kepercayaan Nasabah BRI Unit Kencong Jember - Nabila Ainuz Zahro; Endah Hambarwati; Nurul Erda; Ravika Mutiara Savitrah (CV. ITTC INDONESIA, 2024)
Risk management is a set of procedures and methodologies used to identify, measure, monitor and control risk and increase competition in the banking sector. For that reason, it is important to know the factors that can increase the user confidence of internet banking customers. The purpose of writing this article is to analyze risk management - risks in mobile banking services at BRI Kencong. This study used the quality method